"Freedom of Choice is a Western Concept": Equality, Bodily Rhetoric, and Feminist Fears 1964-1974. Issue 6 (1st November 2020) - Russo, Giusi
Abstract: This article discusses the challenges of promoting women's rights during the development era of the United Nations. The process of decolonization created a fertile terrain to test theories of equality and development for the women of the newly created countries. The UN and its agencies imagined the post-colonial state as one in which development and gender equality were strictly interconnected but such interconnections happened through conflicts over defining women's rights. The sensation of second wave feminism alarmed some of the constituencies involved in designing international policies for the new states. Women delegates from newly independent countries challenged the western-based category of women's rights and welcomed conceptions of rights that were based on the pre-colonial history and the anticolonial resistance period. They had to navigate a goal of equality as well as avoid new western interferences in the constructions of the newly born nation-state.